Legal Certainty and the Protection of Civilian Victims in the Military Criminal Justice System - Wicaksana, Made Adhi Agung; Darmadi, Anak Agung Ngurah Oka Yudistira (IJBLE Scientific Publications Community Inc., 2026)
This study examines the legal vacuum arising from the absence of implementing norms for Article 65 of Law Number 34 of 2004 concerning the Indonesian National Armed Forces (TNI), as well as its implications for legal certainty and the protection of the human rights of civilian victims. Article 65 mandates that TNI personnel who commit general criminal offences be subject to civilian court jurisdiction. However, its implementation is obstructed by Article 74, which makes the applicability of Article 65 contingent upon the enactment of a new law amending Law Number 31 of 1997 concerning Military Courts. Using normative legal research through statutory, conceptual, and comparative approaches, with Australia and the Netherlands as comparative jurisdictions, this study finds that the absence of implementing norms has produced persistent jurisdictional uncertainty. Such uncertainty contradicts the principle of equality before the law and may undermine the right to due process. The study concludes that reform of military jurisdiction through clear and operational legal norms is a prerequisite for ensuring comprehensive justice, legal certainty, and human rights protection for civilian victims.